A FRAMEWORK ENHANCEMENT FOR PROTEIN CODING REGIONS IDENTIFICATION IN EUKARYOTIC DNA SPLICING - AHMAD, MUNEER (2013)
The underlying issues and challenges in protein coding regions identification for Eukaryotic DNA splicing have driven the pronounced attention of researchers. Genome sequence analysis has been widely addressed in literature but there are only a handful of research works and publications on gene identification, especially in the area of protein coding regions identification in the context of exploiting period three property of coding regions. In this scenario, the authors were able to find a few published works on coding regions identification that addressed individual issues involved in better identification but couldn't find any published work that addressed all issues simultaneously.